The Use of Narrative to Provide a Cohesive Structure for a Web Based Computing Course - Martin J. Weller (Journal of Interactive Media in Education, 2000)
Abstract: Narrative has long been used as an educational tool. This article explains how narrative, in the form of popular accounts, has been used to provide context, structure and broad appeal to a large-scale, entry-level university course on Information and Communication Technology (ICT). This course is delivered via the web with online tuition. Students' responses to the use of narrative and the scope of the material has been encouraging. It is argued that narrative performs an enculturation function that is often under-utilised in ICT education.